Tinjauan Pustaka: Peran Tabir Surya dalam Mencegah Photoaging - Tifani, Virginintan Nabila; Hapsari Triandriyani; Sofa Inayatullah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Extrinsic skin aging or photoaging occurs due to repeated and prolonged exposure to ultraviolet (UVA) and ultraviolet B (UVB). Photoaging prevention can be done, one of which is the use of sunscreen. This literature review aims to review the role of sunscreen in photoaging prevention using a variety of existing literature. Sunscreen plays an important role in preventing skin damage caused by sunlight, especially in preventing and repairing skin damage due to sun exposure (photoaging). The addition of antioxidants such as vitamin C, vitamin E, vitamin A, melatonin, polyphenols, Polypodium leucotomos (PLE) extract as well as enzymes such as photoliase and T4N5 has been shown to increase protection against UV, visible light, and infrared-A rays and help repair skin damage. The use of colored sunscreen is recommended for protection from visible light. In addition, education on how to use sunscreen properly, such as reapplying every two to three hours and selecting the appropriate SPF and PA, also plays a big role in maximizing the effectiveness of skin protection from photoaging.